Understanding the leadership experience of Malaysian celebrities participating in political parties and community-based organizations - Heli, Helme; Ismail, Ismi Arif; Krauss, Steven Eric; Abd. Wahat, Nor Wahiza (Human Resource Management Academic Research Society, 2024)
Celebrity leadership has been demonstrated to enhance the significance and guidance of leadership in political parties and community-based organizations. There are regulations in Malaysia pertaining to celebrity leadership and the cultivation of leadership skills inside political parties and community organizations. These methods involve philanthropy and providing support to community-based organizations that tackle diverse social challenges. The aforementioned circumstances have resulted in notable deficiencies in understanding the perceptions of leadership among Malaysian celebrities, their extent of influence in engaging in such roles, strategies for fostering an environment conducive to celebrity leadership, and the obstacles that hinder celebrities from fully realizing their personal and professional potential as leaders within political parties and community organizations. Additionally, it is imperative to analyze the potential of celebrities to promote consciousness regarding community concerns such as poverty, education, healthcare, and the environment. There exist knowledge gaps pertaining to the perspectives of Malaysian celebrities regarding leadership and engagement. This study investigated the leadership roles of Malaysian celebrities in political parties and community groups, with a specific focus on transformational leadership tactics. The aim was to address the existing research gap in this area. This study focuses on the leadership experiences and strategies employed by Malaysian celebrities to establish connections with political parties and community organizations. A total of 12 renowned figures from political parties and community organizations were interviewed by the researcher. The research investigates the leadership positions of Malaysian celebrities, the reasons that impact their engagement, strategies for incorporating leadershipparticipation in political parties and community-based organizations, and the obstacles they encounter.